PELAKSANAAN PROGRAM PEMAGANGAN DALAM NEGERI OLEH DINAS TENAGA KERJA KOTA PEKANBARU TAHUN 2016 - Wiwin Hartanti; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The demands of the workforce of skilled labor encourage job seekers to attend job training and apprenticeship to add to their skills. Pekanbaru City Manpower Office to create and implement employment programs for job seekers to create a program that is the Internal Apprenticeship Program in collaboration with Private Work Training Institute in Pekanbaru city. Total employment after training and apprenticeship in 2016 is 85% where as many as 143 participants are absorbed into the world of work. This means that the implementation of the program in accordance with the expected where the participants who trained and traded to get a job and make their own business (independent). The purpose of this study is to see how the Implementation of Internal Apprenticeship Program by the Municipal Labor Office Pekanbaru Year 2016 and know what factors that influence it. Researchers use the Nakamura and Smallwod theory which mentions that there are three dominant ways to know the success of program implementation: bureaucratic obedience to policies set forth in the Act, Functioning of routine procedures in the implementation of the program and the achievement of program objectives. This research uses qualitative descriptive method, data collection techniques through observation and interview where the parties involved in this research as an informant. The results of this study indicate that the implementation of Internal Apprenticeship Program by the Department of Work in Pekanbaru City in 2016 runs well where the labor absorbed is 85%. This can happen because the three components in the successful implementation of the program, namely the bureaucracy compliance with the policies set forth in the Act, the functioning of routine procedures in the implementation of the program and the achievement of program objectives that are well designed and executed. Factors influencing the Implementation of Internal Apprenticeship Program by the Manpower Office of Pekanbaru City in 2016 is a good coordination between all implementing parties of domestic apprenticeship programs and adequate facilities and infrastructure.Keywords: Implementation, Apprenticeship and Training Institute